THE EFFECT OF VIDEO ON READING COMPREHENSION AND READING INTEREST - Samsul Marfista (PIKTORIAL : Journal of Humanities, 2019)
The Objectives of this study were to get empirical evidence about the difference in reading achievement between students who were taught English by using Video and those who were not. The design of the study was a factorial design of 2 X 2. The samples of the study were taken from the eighth-grade students of SMPN 11 Kota Tangerang Selatan. The design used to take the samples of the study was Nonequivalent control group design. There were two classes that became sample classes, they were 8.1 class and 8.2 class, each class has forty-one students so there were eighty-two students as a sample, 8.1 class was as a controlled class while 8.2 class was as an experimental class. The experimental class was given a video while the controlled class was not. There were two kinds of instruments used for the research. The first instrument was a test and the second one was a questionnaire. The test was aimed at measuring students’ reading comprehension while the questionnaire was aimed at measuring students’ reading interest. The results of the test were in the form of a gained score which was analyzed by using Anova with the significance level is 5%. It was found that the mean score for experimental class was 23 and for controlled class was 22, meanwhile, the modus score of the experimental class was 22 and for control, class was 20 and then the statistical computation on the gained score revealed that the significance value of Video, Reading Interest and both interactions toward reading comprehension had significance value lower than 0.05 (>0.05) while the t-table value 5%. Keywords: Video, Reading Comprehension, Reading Interest